Research on the Support-Free Replacement Method of Suspenders for Long-Span Self-Anchored Rail Special Suspension Bridges - Xiaogang Li; Minglin Zhou; Peng Ding; Ling Luo; Xiangsheng Huang; Xiang Li (Buildings)
To meet the demand of not interrupting traffic during the replacement of suspenders in long-span railway suspension bridges, this research proposes for the first time the application of the unsupported replacement method to the suspender replacement of self-anchored railway suspension bridges. Based on the basic principle of suspension bridge, the safety control index in the process of boom replacement is proposed. Midas Civil 2024 software is used to analyze the structural response of the boom after removal under static force and train load, including the change of cable force of adjacent boom, the displacement of main cable and stiffening beam. The real bridge test was carried out based on the special bridge of Chongqing Egongyan Track. The results show that after the removal of the boom, the cable force of the adjacent boom increases by 42–55%, the main cable is partially twisted but the adjacent joints change little, and the displacement of the stiffened beam meets the specification requirements. When the train is fully loaded, the maximum increase of the cable force of the adjacent boom is 150 kN, the stress increment of the operating boom is far less than the design strength, the increase of the downtorsion of the main cable is only 2.22%, and the displacement of the stiffening beam is within the allowable range. The safety control index and real bridge test results show that the unsupported replacement method is feasible and safe in the replacement of the suspenders of long-span rail suspension bridges, which provides an important reference for related projects.